Impact of primary and recurrent genital herpes on the quality of life of young people and adults: a mixed methods systematic review. Issue 6 (25th June 2022) - Bennett, Clare; Rebafka, Anne; Carrier, Judith; Cook, Sinead; Edwards, Deborah
ABSTRACT: Objective: This review sought to identify the experiences of persons living with genital herpes and what interventions improve the health-related quality of life of young people and adults with primary or recurrent genital herpes. Introduction: Genital herpes is commonly associated with psychosocial challenges. However, a growing body of evidence suggests that its impact can be ameliorated through pharmacological and psychosocial interventions. Inclusion criteria: This review considered English- and German-language studies of community-dwelling males and females, of any ethnicity and geographical location, aged 15 years and older, who had primary or recurrent genital herpes. The quantitative component of the review included studies that reported on the virus' impact on patients' health-related quality of life and/or the efficacy of interventions in improving their health-related quality of life. Studies compared antiviral suppression therapies and psychological interventions with usual care or placebo, or against one another. The qualitative component of the review included studies that investigated the perceptions and experiences of young people and adults with genital herpes. Methods: Eleven databases were searched from January 1980 to March 2020. The JBI approach to mixed methods systematic reviews was followed at each stage of the review, and a convergent segregated approach to synthesis and integration was adopted. Results: A total of 31 publications covering 30 studies were deemed suitable for inclusion. Studies encompassed quantitative (n = 27, across 28 publications), qualitative (n = 1), and mixed methods (n = 2) designs. Critical appraisal scores were variable, particularly among the randomized controlled trials and the analytical cross-sectional studies. All studies were included regardless of methodological quality. The quantitative components identified that depression, illness concern, stress, anxiety, isolation, stigma, and a lowering of self-esteem, self-concept, self-confidence, and health-related quality of life may be experienced by both those newly diagnosed with genital herpes and those with recurrences. It was also identified that genital herpes can have an adverse effect on work or school, sexual relationships, and relationships with friends and family. Depression was found to significantly decrease after self-hypnosis and certain psychosocial interventions. Anxiety significantly decreased following pharmacological treatment, psychosocial interventions, and hypnosis. Psychosocial interventions significantly improved mood, and a self-help module with counseling significantly improved participants' satisfaction with intimate relationships and their self-esteem. Pharmacological treatment significantly improved health-related quality of life; however, there were no significant differences between different active treatment regimens. The qualitative component of the review led to the identification of two synthesized findings: "Disclosure of a diagnosis of genital herpes poses a dilemma for people who have the virus" and "A diagnosis of genital herpes has a significant emotional impact for the individual." Integration of quantitative and qualitative evidence revealed a consensus that a diagnosis of genital herpes has a significant emotional impact for individuals and that disclosure is stressful, affects relationships, and affects health-related quality of life; however, there is a lack of consensus regarding efficacy of different interventions. Conclusions: Genital herpes can lead to extreme emotional, social, relational, and sexual distress, but there is insufficient knowledge concerning which interventions best improve health-related quality of life. More high-quality research is required.